Discipline-specific cognitive factors that influence grade 9 students' performance in chemistry - Zhang, Lina; Wang, Lei; Treagust, David (ROYAL SOC CHEMISTRY, 2021)
Students’ academic performance in chemistry can be the result of a number of cognitive and affective factors. This study explored the influence of the discipline-specific cognitive factors of knowledge structure, cognitive perspectives, and cognitive patterns on grade 9 students' chemistry performance. One instrument measured chemistry academic performance based on concept knowing, application and problem solving. Six tasks with marking keys measured the discipline-specific cognitive factors of knowledge structure, cognitive perspectives, and cognitive patterns. Different groups of grade 9 students participated in pilot tests and the field tests. The quality of the chemistry academic performance instrument and the six tasks was inspected by both expert assessment with six raters and computer-aided inspection including Rasch analysis and Kendall rater-consistency reliability tests. Correlation analysis and multiple regression analysis explored the relationship among academic performance and knowledge structure, cognitive perspectives, and cognitive patterns. According to the results of this research, knowledge structure, cognitive perspective and cognitive pattern all influenced grade 9 students’ chemistry performances; cognitive perspective was the most important factor. Based on these findings, we discuss individual student performance relative to their discipline-specific cognitive factors. We recommend that instruction of discipline-specific learning in chemistry pay attention to each of the three discipline-specific cognitive factors and that tasks be designed to promote the progress of each of these three discipline-specific cognitive factors, especially cognitive perspectives.